2022
DOI: 10.52965/001c.31909
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Proximal Tibia Entry Points for Intramedullary Nailing and Validation of The Lateral Parapatellar Approach as Extra-articular

Abstract: Tibial shaft fractures are the most common long bone injury and are often treated surgically in an attempt to minimize complications. Although treatment options for tibial shaft fractures vary based on factors including open injury, severity of fracture, and soft tissue status, intramedullary nailing in adults has emerged as the preferred definitive option for stabilization. Therefore, the primary purposes of this review and cadaveric study were to evaluate the entry points for reamed tibial nails and the risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Therefore, this may contribute to reducing anterior knee pain. Additionally, in their cadaveric study, Patel et al demonstrated that using the parapatellar approach may not compromise joint capsule integrity reaching the entry point without avoiding the capsule, which was not done in our case series [22].…”
Section: Discussionmentioning
confidence: 70%
“…Therefore, this may contribute to reducing anterior knee pain. Additionally, in their cadaveric study, Patel et al demonstrated that using the parapatellar approach may not compromise joint capsule integrity reaching the entry point without avoiding the capsule, which was not done in our case series [22].…”
Section: Discussionmentioning
confidence: 70%
“…As an alternative to the SP approach, the parapatellar extraarticular approach can be applied to patients with patellofemoral arthritis that have a narrow joint space, which is supposed to be a contraindication for the SP approach. The feasibility of this approach has been proved in a study conducted by Patel et al, in which the LPE approach could be successful accomplished by surgeons who were not special trained [ 23 ]. According to our experience, most surgeons can perform this approach proficiently after 3 to 4 times of practices.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports about alternative tibial IMN insertion techniques exist, including lateral and medial parapatellar intramedullary nailing. They both can be performed without traction and popliteal support and therefore might also be useful in avoiding ACS [ 42 ]. However, in our hospital, and therefore in this study, only IP and SP IMN techniques have been used.…”
Section: Discussionmentioning
confidence: 99%